2021
DOI: 10.1136/bmjopen-2020-043994
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural adaptation and psychometric evaluation of the mainland China version of Nursing Home Survey on Patient Safety Culture Questionnaire: a cross-sectional survey based on 50 nursing homes in China

Abstract: ObjectiveTo provide a validated Chinese-language measurement of the Nursing Home Survey on Patient Safety Culture (NHSOPS) in mainland China. The primary goal is to carry out a transcultural adaptation of the NHSOPS Questionnaire into Chinese and evaluate its psychometric properties.DesignA psychometric evaluation study is constructed. First, the ‘translation–back-translation–cultural adaptation’ and the pretesting procedure were followed to introduce the NHSOPS. Second, a cross-sectional survey was used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It has good reliability and validity, and can be used as an effective tool to evaluate the patient safety culture in China's medical institutions. [11][12][13] We issued an electronic questionnaire to investigate the ET members' perceptions of patient safety and then collected the questionnaires.…”
Section: Hsopsc Electrical Questionnairementioning
confidence: 99%
“…It has good reliability and validity, and can be used as an effective tool to evaluate the patient safety culture in China's medical institutions. [11][12][13] We issued an electronic questionnaire to investigate the ET members' perceptions of patient safety and then collected the questionnaires.…”
Section: Hsopsc Electrical Questionnairementioning
confidence: 99%
“…1. Overall commitment to quality; Researches about safety culture have mainly adopted quantitative research methods (Li et al, 2021;Wang et al, 2019;Wang, Fan, et al, 2020;Zhong et al, 2019), with limited qualitative studies reported (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%